Argyreia nervosa exposures reported to Texas poison centers. Issue 3 (2nd October 2018) - Forrester, Mathias B.
Abstract: The seeds of Argyreia nervosa (Hawaiian baby woodrose) contain lysergamide or lysergic acid amine, an analog for lysergic acid diethylamide. Twenty-nine Argyreia nervosa exposures reported to Texas poison centers during 2000–2018 were identified. Seventy-nine percent of the patients were male; the mean age was 24 years (range 16–53 years). The exposure route was 97% ingestion and 3% inhalation. Ninety-three percent of the exposures occurred at the patient's own residence and 3% at another residence. Fourteen percent of the patients were managed on-site, 69% were already at or en route to a healthcare facility when the poison center was contacted, and 17% were referred to a healthcare facility by the poison center. The medical outcome was 3% no effect, 31% minor effect, 38% moderate effect, 7% major effect, 7% not followed-minimal clinical effects possible, and 14% unable to follow-potentially toxic. The most frequent clinical effects were gastrointestinal (45%) and neurological (41%). The most frequently reported treatments were administration of intravenous fluids (28%) and benzodiazepines (21%).